Elucidating the physical origins of the animal magnetic sense by cavity-enhanced spectroscopy - Golesworthy, M (2021)
Many animal species have the ability to navigate using the Earth’s magnetic field. This is particularly true of migratory birds, who are able to fly thousands of kilometres only to nest in exactly the same place year on year. The best current hypothesis as to the method by which this magnetoreception – the ability to sense magnetic fields – takes place is that of magnetically sensitive radical pairs in cryptochromes – blue light photoreceptors found in the retinae of birds and other animals. Chapter 1 explores the theory needed for understanding the phenomenon of magnetoreception, especially spin chemistry.